2013
DOI: 10.1364/oe.21.021897
|View full text |Cite
|
Sign up to set email alerts
|

A flatbed scanner for large-area thickness determination of ultra-thin layers in printed electronics

Abstract: Enabling solution-based printing techniques for sub-100 nm thin semiconductors for the application in large-area organic electronics is a challenging task. In order to optimize the process parameters, the layers have to be characterized on a large lateral scale while determining the nanometer thickness at the same time. We present a lateral and vertical resolving measurement method for large-area, semi-transparent thin films based on optical interference effects. We analyzed the RGB color images of up to 150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Analysis by profilometry is disadvantageous because of long measuring times for stitching of continuous single measurements. We used reflectometric thin-film recordings (vide infra), supplemented by tactile profilometry for each printed sample. This optical method for evaluating the layers and their printing quality gives sufficient information about layer homogeneity including surface waviness or film defects and therefore gives an evaluation of the suitability of the printed films for OLED applications …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis by profilometry is disadvantageous because of long measuring times for stitching of continuous single measurements. We used reflectometric thin-film recordings (vide infra), supplemented by tactile profilometry for each printed sample. This optical method for evaluating the layers and their printing quality gives sufficient information about layer homogeneity including surface waviness or film defects and therefore gives an evaluation of the suitability of the printed films for OLED applications …”
Section: Resultsmentioning
confidence: 99%
“…We used reflectometric thin-film recordings (vide infra), supplemented by tactile profilometry for each printed sample. This optical method for evaluating the layers and their printing quality gives sufficient information about layer homogeneity including surface waviness or film defects and therefore gives an evaluation of the suitability of the printed films for OLED applications Figure shows the results of the printed toluene inks (Figure a–c, 50 g L –1 ), mesitylene/anisole inks (Figure d–f, 50 g L –1 ), and pure mesitylene inks (Figure g–i, 20 g L –1 ) printed on indium tin oxide (ITO)-covered PET sheets (15 × 5 cm 2 , SI, S5a–c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…His method was applied to a dual-layer hard coating on a PET film. Bornemann presented thickness measurements for large-area and multi-layer printed devices using RGB scanning images and color contrast [15]. The method was tested using an organic semiconductor and showed sub-100 nm accuracy.…”
Section: Of 14mentioning
confidence: 99%
“…8,9 Even though the viscosity magnitude of 1 70 and 1 176 is appropriate for gravure printing, both samples show significant shear thinning at higher shear rates, which would make them less ideal as functional inks since the non-Newtonian nature of the fluid favors hydrodynamical instabilities during the printing process. 10,3 Moreover, it was observed that 1 70 and 1 176 gel at concentrations above 10 g L −1 and 5.4 g L −1 , respectively.…”
mentioning
confidence: 96%